2011
DOI: 10.1371/journal.pone.0024306
|View full text |Cite
|
Sign up to set email alerts
|

Ranking Candidate Disease Genes from Gene Expression and Protein Interaction: A Katz-Centrality Based Approach

Abstract: Many diseases have complex genetic causes, where a set of alleles can affect the propensity of getting the disease. The identification of such disease genes is important to understand the mechanistic and evolutionary aspects of pathogenesis, improve diagnosis and treatment of the disease, and aid in drug discovery. Current genetic studies typically identify chromosomal regions associated specific diseases. But picking out an unknown disease gene from hundreds of candidates located on the same genomic interval … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 43 publications
0
50
0
Order By: Relevance
“…This has been the computational approach most commonly used to create disease-relevant interaction networks (Chuang et al 2007;Zhao et al 2011). This procedure yielded the interaction network PPI D (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This has been the computational approach most commonly used to create disease-relevant interaction networks (Chuang et al 2007;Zhao et al 2011). This procedure yielded the interaction network PPI D (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is well confirmed that the propensity of many diseases can be reflected in a difference of gene expression levels in particular cell types40. For this reason, genes showing a different expression levels in control crowds (i.e.…”
Section: Methodsmentioning
confidence: 88%
“…Starting with a group of SpA-active genes as seeds, we applied a Katz' centrality based index [33] to prioritize candidate genes in the PPI network [15]. Given a weighted human interactome represented as a matrix W corresponding to the interaction strength between genes, and a set D of k known disease-active genes as seeds, we define vector x = ( x 1 , x 2 ,..., x n ) T as initially known activity of genes in the disease, with x i = 1 if gene i is in the set D, x i = 0 otherwise.…”
Section: Resultsmentioning
confidence: 99%